PTH-098 Anti-tnfs more frequently stopped due to loss of response in british asians with crohn's disease: a single centre retrospective analysis. (17th June 2017) - Gadhok, R; Gordon, H; Sebepos-Rogers, G; Baillie, S; Akbar, S; Ahmad, OF; Cooper, B; Lindsay, JO
Abstract : Introduction: The prevalence of IBD among British Asian populations matches that of British Caucasians within 2 generations of migration. However response to treatment within this population has not been reported. This study investigates whether indications for and response to anti TNF therapy vary with ethnicity. Method: The electronic records for patients under follow up between Sept 2015 and Sept 2016 at a large London IBD centre were studied, and patients ever prescribed anti-TNF were identified. Data collected included: disease onset and phenotype, indication for and time to first anti-TNF, and duration and indication for withdrawal (sustained remission, primary non response, loss of response >3 months or intolerance). Ethnicity was ascertained as per UK standard coding and categories grouped as Caucasian, Asian or Black. Results: 484 patients were identified from electronic records. 131 patients were excluded; 22 with mixed ethnicity, the remainder with incomplete records. Following exclusions, 223 Caucasian, 105 Asian and 25 Black patients remained (Total n=353). 245 received infliximab, 105 adalimumab, and 2 unspecified. The mean age was 33.3 years (16-74) with 59.2% (n=209) male and 41.8% (n=144) female. 77.6% (n=274) had CD, 19.2% (n=68) had UC, the remainder had IBD-U. All UC and 63.91% (n=175) CD patients were treated for exclusively luminal disease; the remainder had luminal with either fistula or perianal disease. Indications did not vary with ethnicity (Chi sq. p=0.1697). There was no difference in age at diagnosis with ethnicity for CD or UC. The median (IQR) disease duration to first anti-TNF varied with ethnicity: Caucasians 7.8 (2.3–12.6) years; Asians 4.3 (2.0–7.3) years; Black 4.9 (2.1–9.7) years (Kruskal-Willis, p=0.0014, n=314). Asian patients with CD were prescribed anti-TNF a median 3.8 years earlier in disease course than Caucasians (Mann Whitney p=0.0002 n=229). 190 patients had stopped anti-TNF therapy at the time of review; 165 had a clearly documented stop and start date. Of these, the median (IQR) duration to stopping was 1.2 (0.5–2.3) years and did not vary with ethnicity (Kruskal-Wallis 0.9589). The indication for stopping anti-TNF varied with ethnicity(Chi Sq p=0.0010). Sub analysis of CD only showed that fewer Asians stopped due to sustained remission (Chi Sq with Yates correction p=0.0392). This trend was not seen within UC (p=0.1488) Conclusion: Asian patients with IBD receive an anti-TNF sooner, but are more likely to have loss of response and are less likely to experience sustained remission. Disclosure of Interest: None Declared